Surface biocalcification for concrete - Goh, Zhao Jia (2017)
With the world getting urban centric, the building of concrete structures swiftly multiplies. Despite the widely usage of concrete, these structures are still susceptible to deterioration due to the exposure to water, oxygen and aggressive compounds brought about by the environment. Treatment of the concrete is one way to ‘heal’ it, enabling the rate of deterioration to be reduced or the damaged structures to be repaired. In recent years, research studies have been carried out to investigate the use of an environmentally friendly method to repair concrete cracks as opposed to more conventional approaches. This method is known as the ‘‘Microbial Induced Calcite Precipitation’’ (MICP) method which involves ureolytic bacteria inducing calcium carbonate precipitation inside the cracks of concrete. The effectiveness of this MICP method is relatively dependent on the quantity of calcium carbonate deposited within the concrete cracks. This project was carried out to improve the effectiveness of the MICP method for concrete repair by reducing the steps taken in the MICP process. As conventional MICP typically requires a separate introduction of the Urease Producing Bacteria (UPB) and cementation solution to the concrete, this research aims to further enhance this method by tweaking current procedures to inject both solutions at the same time into the concrete. The calcite precipitation by both 1-step MICP and 2-step MICP had been observed to be similar when yeast was introduced to the treatment solutions. The experimental results showed that the water flow through the concrete crack by 2-step MICP does not differ much from the 1-step MICP with the addition of yeast. On the other hand, the 1-step MICP showed a huge decrease in water permeability once the UPB’s pH had been adjusted to 5 and with the addition of yeast to aid the process of MICP.